The dreaded osteonecrosis of femur following chronic steroid therapy: a case series from a dermatologist’s eye - Ponnuswami, Abiram; S., Cordelia Babitha; Muralidhar, Krishnakanth; Sundaram, Murugan (International Journal of Research in Dermatology, 2020)
Corticosteroids, undoubtedly, is the saving grace of many patients ailing from a variety of inflammatory and autoimmune dermatoses. But it is not free of side effects, some being crippling enough to subject the patient to huge amounts of morbidity. Here we report a series of cases – Vesiculobullous diseases and Lupus Erythematosus - with prolonged oral steroid therapy that lead to osteopenia and osteonecrosis of the femur.